2010
DOI: 10.1200/jco.2009.27.2021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Recurrences in Tamoxifen and Anastrozole Treated Women: An Exploratory Analysis From the ATAC Trial

Abstract: These results confirm the poorer prognosis of obese women with early-stage breast cancer. Recurrence rates were lower for anastrozole than tamoxifen for all BMI quintiles. Our results suggest that the relative efficacy of anastrozole compared to tamoxifen is greater in thin postmenopausal women and higher doses or more complete inhibitors might be more effective in overweight women, but this requires independent confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
235
1
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(266 citation statements)
references
References 26 publications
12
235
1
11
Order By: Relevance
“…In the ATAC study women with BMI of >35 kg/m 2 were more likely to relapse than those with a BMI of <23 kg/m 2 and had significantly more distant recurrences [28]. Similar results were recorded in the German BRENDA-cohort [29].…”
Section: Aromatasesupporting
confidence: 68%
“…In the ATAC study women with BMI of >35 kg/m 2 were more likely to relapse than those with a BMI of <23 kg/m 2 and had significantly more distant recurrences [28]. Similar results were recorded in the German BRENDA-cohort [29].…”
Section: Aromatasesupporting
confidence: 68%
“…In the three trials, an aromatase inhibitor was associated with improved outcomes compared with that of tamoxifen at all BMI values. Notably, BMI did not significantly interact with letrozole (vs. tamoxifen) in the BIG 1-98 trial (25), whereas the ATAC investigators concluded that the relative benefit of anastrozole (vs. tamoxifen) may be more pronounced in women of a lower weight (24). These findings do not support the notion that BMI can predict the benefit of aromatase inhibitors (vs. tamoxifen) as adjuvant therapies in postmenopausal patients with breast cancer (27).…”
Section: Discussionmentioning
confidence: 92%
“…This theory has been supported by the results of clinical studies with anastrazole and letrozole showing a reduction in the efficacy of these aromatase inhibitors with increasing BMI (8,9). Plasma estradiol and estrone sulfate levels in obese patients remain significantly elevated in comparison to nonobese patients following letrozole treatment (10), indicating that this reduced response rate may be related to suboptimal inhibition of obesity-associated aromatase activity.…”
Section: Introductionmentioning
confidence: 88%